Atinide iron hoop body thin film material and preparation method and application thereof

Actinide iron ring film materials prepared by spin coating method are solved by irradiation or LED light reduction methods, and have strong iron ring properties and long-range order properties of film materials, with potential information storage and quantum computing applications.

CN119639023AActive Publication Date: 2025-03-18PEKING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510175475.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The existing iron ring materials have difficulties in synthesis and characterization, especially the difficulty in preparing thin film materials with strong iron ring properties and long-range order, which limits their application in the fields of information storage and quantum computing.

Method used

Actinide iron ring film material is prepared by spin coating method, using chemical components of cyclodextrin, actinyl ions and alkali metal ions, and the preparation of the iron ring film is achieved by irradiation reduction or LED light reduction method to ensure that the material has iron ring moment and super exchange capacity.

Benefits of technology

The millimeter-level actinide iron ring film has been prepared, with strong iron ring order and room temperature ferromagnetic characteristics, and can have potential applications in the fields of information storage and quantum computing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639023A_ABST
    Figure CN119639023A_ABST
Patent Text Reader

Abstract

The invention discloses an actinide iron hoop body thin film material as well as a preparation method and application thereof, and belongs to the technical field of iron materials. The actinide iron ring body thin film material is a crystal thin film prepared by a spin coating method, and chemical components of the actinide iron ring body thin film material comprise cyclodextrin, actinide ions and alkali metal ions. Firstly, the actinide cyclodextrin crystal thin film is prepared on a substrate through a spin-coating method, and the thin film is good in compactness and controllable in thickness; and high-efficiency controllable reduction of the crystal film is realized through two ways of irradiation reduction or LED photoreduction, so that the iron ring body film is obtained. The actinide iron hoop body thin film material has the basic properties of iron hoop bodies, and lays an important foundation for development of iron hoop body devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an iron ring material, in particular to an actinide iron ring film material and a preparation method and application thereof, belonging to the technical field of ferrous materials. Background Art

[0002] Ferroelectric materials refer to a class of materials that are polarized under an external field and whose polarization properties are reversed with the external field and produce a hysteresis effect. The three common ferroelectrics include ferromagnetism (spontaneous magnetization), ferroelectricity (spontaneous polarization) and ferroelasticity (spontaneous strain), which are polarized under the action of external magnetic field, electric field and stress field and reversed with the change of external field (A.Zimmermann, D. Meier&M. Fiebig. Ferroic nature of magnetic toroidal order.[J]. Nature Communications 2014, 5, 4796). Ferromagnetism and ferroelectricity break the time reversal symmetry and space inversion symmetry respectively, while the time reversal symmetry and space inversion symmetry of ferroelasticity remain unchanged. According to theoretical speculation, there should be a material with a single order parameter that breaks both spatial inversion symmetry and time inversion symmetry. Scientists call it ferrotoroidic materials (GT Rado. Observation and Possible Mechanisms of Magnetoelectric Effects in a Ferromagnet [J]. Physical Review Letters 1964, 13, 335-337).

[0003] Theoretical physicists have made great contributions to the prediction of the properties of ferroic materials, including: (1) proving that the premise for the formation of ferroicity is the formation of antiferromagnetic coupling between magnetic ions; (2) proposing 31 magnetic point groups that can satisfy ferroicity, revealing the symmetry of ferroic materials; (3) proposing four criteria for ferroic materials: i. long-range order below a certain temperature; ii. the existence of ferroic domains; iii. the existence of a phase transition temperature; and iv. a significant enhancement of the macroscopic magnetic susceptibility near the transition temperature (S. Gnewuch, EE Rodriguez. The fourth ferroic order: Current status on ferrotoroidic materials [J]. J. Solid State Chem. 2019, 271: 175-190). There have been many studies exploring the synthesis of ferroic materials, but there are currently few examples that fully demonstrate ferroicity (such as LiCoPO4) (S. Gnewuch, EE Rodriguez. The fourth ferroic order: Current status on ferrotoroidic materials [J]. J. Solid State Chem. 2019, 271: 175-190). This is mainly due to two reasons: (1) Synthesis is difficult. It is very difficult to build a toroidal magnetic moment and keep it in long-range order. (2) Characterization is difficult. For traditional hard ferroic materials, to prove long-range order, second harmonic generation spectroscopy (SHG) or spherical neutron polarization analysis (SNP) is required, and the millimeter-scale single crystals required for these experiments are difficult to grow (S. Gnewuch, EE Rodriguez. The fourth ferroic order: Current status on ferrotoroidic materials [J]. J. Solid State Chem. 2019, 271: 175-190).

[0004] LiCoPO4 is the most studied ferroic material and has the above four criteria. The method by which LiCoPO4 forms ferroic moments is to form large and small moments through the tilt of spin electrons in the unit cell, which presents a net ferroic moment overall. Although this method can form ferroic moments, the net value of the ferroic moments is very low, and the ferroic properties of the formed material are not strong. At the same time, the magnetic ions Co that form the ferroic moments 2+There is no super exchange interaction between them, and the formed ferroic ring is not stable enough. More importantly, the LiCoPO4 material based on the inorganic skeleton itself has no scalability, and it is not easy to carry out functional modification and subsequent application transformation. Another widely-watched material with ferroic ring properties is the single-molecule ring body. It has the advantages of super exchange and easy modification of the organic skeleton (X. Li, J. Wu, J. Tang, BL Guennic, W. Shi, P. Cheng. A planar triangular Dy3+ Dy3single-molecule magnet with a toroidal magnetic moment [J]. Chem. Commun. 2016, 52: 9570-9573), but its disadvantage is that it does not have the long-range order of the ring moment, so it does not meet all the standards of the ferroic ring material and is not a true ferroic ring. Because it cannot show ferroic ring properties in the long range, it is very limited in device application.

[0005] Actinides, especially actinide acyl ions (UO2 + , NpO2 2+ , PuO2 2+ , AmO2 2+ , CmO2 2+ ) has a strong spin-orbit coupling effect (Meihaus, KR&Long, JR Actinide-based single-molecule magnets[J]. Dalton Trans. 2015, 44: 2517-2528) and strong superexchange effect (Belkhiri, L., Guennic, BL&Boucekkine, A. DFT investigations of the magnetic properties of actinidecomplexes [J]. Magnetochemistry 2019, 5:15), it is easier to construct long-range magnetic ordered structures than transition metals and lanthanide metals.

[0006] CN116836406A successfully constructed an actinide soft iron ring material based on actinide elements and cyclodextrin. Compared with the aforementioned LiCoPO4 material, the actinide soft iron ring supramolecular crystal material has stricter and stronger iron ring properties, and has the following six characteristics of iron rings: (1) long-range order below a certain temperature; (2) the existence of iron ring domains; (3) the existence of a phase transition temperature; (4) a significant enhancement of the macroscopic magnetic susceptibility near the transition temperature; (5) a truly geometric ring arrangement of magnetic moments; and (6) the existence of superexchange interactions between magnetic ions.

[0007] The application of ferroxene materials is mainly reflected in two aspects: (1) Information storage. The inherent electromagnetic coupling effect of ferroxene materials makes them have great potential applications in the field of information storage. Due to the characteristics of spontaneous magnetization and electric polarization, ferroxene materials can realize electric field control of magnetic field. Compared with the working mode of changing the current to change the magnetic field and then change the stored information, the working mode of electric field controlling the magnetic field can greatly reduce energy consumption and improve the reading and writing speed. The storage devices developed based on this system can realize low-power fast information storage and reading and writing. (2) Quantum computing. Ferroxene materials have the property of long-range magnetic order and can be used to create stable quantum states. The magnetic ions in the ferroxene have the quantum Hall effect, which means that they can exhibit fractional spin current and other interesting phenomena. This makes them very suitable for use in quantum spin electronic devices, which use spins instead of electrons to store and process information.

[0008] At present, the field of ferroic magnetoelectric composites is still at the stage of material preparation and basic property research, and no research has explored the thin film preparation and device processing technology of ferroic magnetoelectric composites. Although the previously prepared actinide soft ferroic magnetoelectric supramolecular crystals have excellent ferroic properties, they must be processed into electronic devices if they are to be truly applied, such as information storage or quantum computing. However, the crystal powder belongs to bulk materials, and there are still problems such as insufficient crystal size and difficulty in processing. The development from bulk materials to thin film materials can achieve material flatness, which can largely solve the above problems and realize micro-nano processing and device manufacturing. It can be said that it is an indispensable step towards practical applications in the future (J. Ma, JM Hu, Z. Li, & C. W. Nan. Recent progress in multiferroic magnetoelectric composites: from bulk to thin films. [J]. Adv. Mater. 2021, 23: 1062-1087).

[0009] The preparation of thin films of inorganic crystals is often achieved through physical vapor deposition, chemical vapor deposition, atomic layer deposition and other technologies, which have the problems of complex preparation process and high production cost. For organic crystals, due to their strong solubility, good volatility and structural flexibility, they are particularly suitable for the preparation of thin films by spin coating. At the same time, by controlling the parameters of spin coating, such as spin coating speed, drying temperature, etc., the structure of the film can be controlled, thereby changing the performance. Summary of the invention

[0010] The purpose of the present invention is to provide an actinide ferroxene thin film material and a preparation method thereof. The material has the basic properties of ferroxene crystals, long-range ferroxene moments and super exchange capacity between magnetic ions, and the film size reaches the millimeter level, which is sufficient for processing into electronic devices, laying the foundation for the development of ferroxene devices.

[0011] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: An actinide iron ring thin film material is a crystal thin film prepared by a spin coating method, and its chemical components include cyclodextrin, actinyl ions and alkali metal ions, wherein the cyclodextrin can be α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, macrocyclodextrin and other cyclodextrins; the actinyl ions are selected from UO2 + , NpO2 2+ ,NpO2 + ,PuO2 2+ , AmO2 2+ , CmO2 2+ One or more of; the alkali metal ion is selected from Li + , Na + , K + , Rb + , Cs + One or more of .

[0012] First, a uniform actinyl cyclodextrin crystal film is prepared by spin coating. The uranyl cyclodextrin crystal film must be reduced to pentavalent uranyl by irradiation reduction or photoreduction to obtain an iron ring film. For other actinyl cyclodextrin crystal films, iron ring properties are obtained without reduction.

[0013] Due to the strong superexchange capacity of actinides and the annular molecular skeleton, high electron density and confined coordination of cyclodextrin, the obtained actinide iron ring has stronger iron ring order and the order transition temperature (Curie temperature, T c ) above room temperature, and has significant practical application value.

[0014] In the preparation method of the actinide iron ring thin film material of the present invention, the first step is to prepare an actinide cyclodextrin crystal film by spin coating a mother solution containing actinyl nitrate, cyclodextrin and alkali metal hydroxide on a substrate. The mother solution solvent is ultrapure water, and the molar ratio of actinyl nitrate: cyclodextrin: alkali metal hydroxide in the composition is in the range of 1:2:10 to 1:2:50, wherein the concentration of actinyl nitrate is preferably in the range of 10-80 mM.

[0015] By adjusting the spin coating conditions, the growth of crystal films can be affected, and the thickness, dominant crystal plane and other structural information of such crystal films can be changed, thereby achieving the regulation of the performance of crystal films. The adjustment parameters of the spin coating method mainly include substrate selection, sample addition method, spin coating speed, spin coating time, and drying method. The substrate can be selected from single crystal silicon wafers, quartz glass, sapphire, metal substrates, etc. The sample addition method adopts a static sample addition method, and the sample addition amount should be kept to cover 1 / 3 to 1 / 2 of the substrate area. When using silicon wafers as spin coating substrates, preferably, the silicon wafers are chemically cleaned with piranha solution before spin coating. The spin coating speed affects the thickness of the film. Preferably, the spin coating speed is 1000 to 10000 rpm and the spin coating time is 0.5 to 10 min. The drying method is natural drying or heating drying (<100°C). After drying, the film exhibits colored diffraction fringes.

[0016] In the method for preparing the actinide iron ring thin film material of the present invention, the second step is the reduction of the actinyl cyclodextrin crystal film. The uranyl cyclodextrin crystal film must be reduced, while other actinyl cyclodextrin crystal films may or may not be reduced. There are two reduction methods, including irradiation reduction method and LED light reduction method.

[0017] The radiation reduction method uses γ-rays as the emission radiation, and the radiation source can be 60 The irradiation dose affects the degree of reduction. The irradiation dose used in the present invention ranges from 100 to 800 kGy, and the irradiation dose rate ranges from 100 to 800 Gy / min.

[0018] The LED photoreduction method uses white light LED as the light source, and the wavelength range of the light is between 400 and 700 nm, with two peaks at 480 nm and 550 nm. During the irradiation process, the light source is close to the sample film, the light source power selection range is 10 to 100 mW, and the irradiation time range is 1 to 100 h.

[0019] The present invention studies the basic properties of the actinide iron ring film material, such as time reversal symmetry breaking and space inversion symmetry breaking.

[0020] Time reversal symmetry breaking is mainly verified by magnetic measurement, using a standard magnetic measurement comprehensive system (PPMS) to measure variable temperature magnetic susceptibility and hysteresis loops. Spatial inversion symmetry breaking is verified by second harmonic generation spectroscopy (SHG) testing, and the SHG signal of the variable power test is used to illustrate the existence of a non-centrosymmetric structure in the crystal, and then the property of spatial inversion symmetry breaking is deduced. Magnetic data show that this type of actinide iron ring thin film material has room temperature ferromagnetic characteristics, and the zero field cooling (ZFC) and field cooling (FC) curves are clearly separated, indicating that the material has a strong magnetic coupling interaction. The transition temperature under an external field of 2000 Oe is about 280 K. The SHG results show that the crystal has a significant non-centrosymmetric structure, which can be proved by combining the crystal chirality to have a spatial symmetry breaking property. The actinide ferroxene film material exhibits the basic properties of ferroxene, with long-range ferroxene moments and superexchange capacity between magnetic ions; the film size reaches the millimeter level, which is sufficient for processing into electronic devices; at the same time, due to its adjustable composition and thickness, its structure can be adjusted according to different application requirements to achieve better performance.

[0021] Beneficial effects of the present invention: The present invention provides an actinide iron ring body supramolecular film and a preparation method thereof. The present invention prepares a millimeter-scale actinyl cyclodextrin crystal film for the first time by a spin coating method, and can change the film thickness and thus control the performance by adjusting the mother solution concentration and the spin coating speed, which opens up a new idea for the preparation of cyclodextrin supramolecular materials. At the same time, by utilizing the high electron density and confined coordination environment of cyclodextrin, the present invention can achieve efficient reduction of uranyl and stabilize it to pentavalent, thereby obtaining an iron ring body film. For other actinyl cyclodextrin materials, an iron ring body film with specific magnetic properties can be obtained without reduction. The preparation method has mild conditions, and the irradiation reduction method and the LED light reduction method have the advantage of being non-destructive compared to the xenon lamp reduction, and can better maintain the structure of the crystal film. In addition, the present invention solves the following technical problems and achieves the following beneficial effects: 1) Preparation of large-size ferroxene thin films based on substrates. Previously, ferroxene was mostly concentrated in the field of inorganic crystals, and there was a lack of research on film preparation and properties. The planar structure is the basis for integrated addition and device manufacturing. The preparation of ferroxene thin film structures, especially ferroxene thin films based on silicon substrates, is of great practical significance for the application of ferroxene in the field of electronic devices. Since the raw materials of the film are organic molecules and metal ions, the rapid growth and preparation of crystal films can be achieved by spin coating, which is an advantage that inorganic crystals do not have. For silicon substrates, since cyclodextrin and metal ions are hydrophilic, and silicon substrates are hydrophobic, spin coating directly on silicon substrates cannot form a film. The present invention uses piranha solution to chemically clean silicon wafers, so that a thin layer of silicon dioxide molecules is generated on the surface of the silicon wafer. Due to the hydrogen bonding between hydroxyl groups and water molecules, the silicon wafer changes from hydrophobic to hydrophilic, thereby solving the problem of difficulty in growing thin films on silicon wafers.

[0022] 2) The spin coating method used in the present invention has the following characteristics and advantages: (a) By screening parameters such as substrate selection, mother solution dripping method, spin coating speed, spin coating time, drying temperature, etc., the optimal conditions for film growth are obtained, forming an optimal method for preparing this type of actinide iron ring film; (b) The crystals grown based on the film have better crystallinity, and the dominant crystal plane can be adjusted by changing the spin coating speed and time, that is, the crystal growth direction can be regulated, thereby achieving performance regulation; (c) From the application point of view, the preparation of the thin film material realizes the flattening of the iron ring material, laying an important foundation for device processing and large-scale integration.

[0023] 3) Development of a mild and controllable reduction method. In previous studies, pentavalent uranyl crystal films were prepared using xenon lamp reduction, but this method still has problems such as insufficient penetration depth, damage to the crystals due to thermal effects, and insufficient reduction ratio. The present invention has developed two novel reduction methods, irradiation reduction and LED light reduction, which enrich the reduction methods. Among them, irradiation reduction has the advantages of high penetration depth, small thermal effect, and high reduction ratio; while LED light reduction has the advantages of no thermal effect damage, easy to control the reduction ratio, and easy to scale up. The two new reduction methods each have their own advantages and disadvantages, which can well solve several problems of previous xenon lamp reduction and have greater application potential in future applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Optical micrograph of the uranyl cyclodextrin crystal film prepared in Example 1.

[0025] Figure 2 Electron micrograph of the uranyl cyclodextrin crystal film prepared in Example 1.

[0026] Figure 3Scanning electron microscope (SEM) images and energy dispersive X-ray spectra (EDS spectra) of the uranyl cyclodextrin crystal film prepared in Example 1. (a) SEM images; (b) C element spectrum; (c) O element spectrum; (d) Cs element spectrum; (e) U element spectrum; (f) Si element spectrum.

[0027] Figure 4 Thickness curves of uranyl cyclodextrin crystal films at different spin coating speeds in Example 1.

[0028] Figure 5 XRD spectra of uranyl cyclodextrin crystal thin films at different spin coating speeds in Example 1. (a) XRD spectrum of thin films prepared at 8000 rpm; (b) XRD spectrum of thin films prepared at 2000 rpm.

[0029] Figure 6 EPR spectra of the film samples at different LED light reduction times in Example 1. (a) EPR spectrum of the sample irradiated with LED for 3 h; (b) EPR spectrum of the sample irradiated with LED for 6 h; (c) EPR spectrum of the sample irradiated with LED for 9 h.

[0030] Figure 7 XPS spectra of the thin film samples with different LED light reduction times in Example 1. (a) XPS U4f fine spectrum of the sample irradiated with LED for 3 h; (b) XPS U4f fine spectrum of the sample irradiated with LED for 6 h; (c) XPS U4f fine spectrum of the sample irradiated with LED for 9 h.

[0031] Figure 8 Temperature-dependent magnetic susceptibility curve of the iron ring film prepared in Example 1 (external field is 400 Oe, temperature range is 4K~300 K).

[0032] Fig. 9 Magnetic hysteresis loop of the iron ring film prepared in Example 1 (temperature is 4 K, scanning range is -1 T to 1 T).

[0033] Fig.10 SHG spectrum of the iron ring film prepared in Example 1. (a) SHG spectrum with variable power; (b) SHG signal intensity versus power (the signal intensity and power are both de-logarithmized and plotted, with a slope of about 2, which is consistent with the characteristics of the SHG signal). DETAILED DESCRIPTION

[0034] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present invention belong to the scope of protection of the present invention.

[0035] Hereinafter, embodiments and comparative examples are given to explain the embodiments of the present invention in more detail. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0036] Materials and Methods 1. Experimental Materials Cesium hydroxide (50%wt, Aladdin); γ-cyclodextrin (>99%, Inokai); uranyl nitrate (used after recrystallization and purification). Ultrapure water was used in the experiment.

[0037] 2. Experimental Methods The spin coating experiment used an EZ4-S-PP mini spin coater; the film thickness was measured using a step profiler (DektakXT, Bruker) from the Peking University Micro-Nano Platform; the photoreduction experiment used an LED light source (Zhongke Jinyuan) and 60 Co radiation source (Peking University); X-ray photoelectron spectroscopy (XPS) was detected and data were collected on the ESCALAB250Xi spectrometer using Al-Kα rays (λ=1.3371Å); electron paramagnetic resonance (EPR) was tested and data were collected on the Magnettech ESR5000 instrument produced by Bruker; DC magnetic susceptibility, AC magnetic susceptibility and hysteresis effect were tested and data were collected on the MPMS-3 produced by Quantum Design. SHG data were measured using a Raman microscopy measurement system (WITec alpha 300R).

[0038] Example 1 (1) Preparation of uranyl cyclodextrin crystal film Mother liquor preparation Weigh UO2(NO3)2∙6H2O (0.251 g, 0.5 mmol) and γ-cyclodextrin (1.297 g, 1 mmol), dissolve in 5.0 mL ultrapure water, quickly add 50 wt% CsOH (2.998 g, 10 mmol), shake to fully disperse, add ultrapure water to make up to 10.0 mL, and store in a cool place away from light.

[0039] Spin coating thin films Use a pipette to take 2 to 3 drops of the mother solution and add them to a 10*10 mm polished silicon wafer (cleaned with piranha solution at 100°C). Set the spin coating speed to 4000 rpm, the spin coating time to 120 s, and the acceleration to 100 rpm / s.

[0040] After the spin coating is completed, the silicon wafer is heated and dried on a heating plate to completely evaporate the solvent to obtain a crystal film.

[0041] (2) Characterization of uranyl-cyclodextrin crystal films Crystal morphology observation like Figure 1 As shown in the optical micrograph, it can be seen that the film has good density, large size (millimeter level) and is relatively uniform. At the same time, small crystal samples are dispersed on the surface of the crystal film.

[0042] like Figure 2 As shown in the electron micrograph, it can be seen that the film is actually a polycrystalline film, with countless small crystals stacked together to form a large polycrystalline film. Figure 3 It can be seen that the crystals contain C, O, U, and Cs elements, and are evenly distributed, indicating the successful preparation of the crystal film.

[0043] Film thickness-spin coating speed curve Films of different thicknesses were prepared by controlling the spin coating speed, and the film thickness was measured by a step profiler. For each sample, the film thickness of three different regions was measured, the average film thickness and standard deviation were calculated, and a film thickness-spin coating speed curve was established, such as Figure 4 shown.

[0044] Crystal face characterization and control of dominant crystal faces like Figure 5 As shown in the figure, the crystal film quality, dominant crystal plane and other structural information were analyzed by powder XRD. It can be seen that compared with the powder crystal, the diffraction peak intensity of the film crystal is significantly improved, that is, the crystallinity is greatly improved. At the same time, at a low speed such as 2000 rpm, the dominant crystal plane is around 28.5°, while at a high speed, the 28.5° crystal plane disappears and the growing crystal plane tilts toward a low diffraction angle. This example shows that the crystal growth direction can be controlled by adjusting the spin coating speed, which will ultimately affect the performance of the ferroxene film.

[0045] (3) Preparation of ferrocyclite film by reduction of uranyl cyclodextrin crystal film Radiation reduction The uranyl cyclodextrin crystal film was placed in a nitrogen-protected sample tube. 60Irradiation under Co radiation source, irradiation dose rate is 100 Gy / min, irradiation dose is 600 kGy. Compared with xenon lamp reduction, irradiation reduction can increase the reduction rate of crystals from about 70% to nearly 90%, and the reduction ratio is greatly improved. In addition, the reduction degree of the sample can be controlled by changing the irradiation dose. After irradiation, the film sample turns dark brown under the microscope.

[0046] LED light restoration The uranyl cyclodextrin crystal film was placed in a light protector to isolate water and oxygen. The light protector containing the sample film was placed under an LED light source with an irradiation power of 100 W and an irradiation time of 6 h. By adjusting the irradiation time, the reduction degree of the crystal can be controlled to obtain iron ring films with different reduction ratios. Figure 6 It can be seen that with the increase of reduction time, the EPR signal of the film is constantly increasing. Figure 7 It can be seen that as the reduction time increases, the reduction ratio continues to increase.

[0047] (4) Characterization of the properties of iron ring films Magnetic research The MPMS-3 instrument was used to measure the temperature-dependent DC magnetic susceptibility and hysteresis loop. Figure 8 It can be seen that the film exhibits a characteristic ferromagnetic signal, and the field cooling (FC) and zero field cooling (ZFC) curves are separated, indicating that there is magnetic coupling in the iron ring film and the transition temperature is above 250 K. Fig. 9 It can be seen that the iron ring has an obvious hysteresis loop, which is consistent with the characteristics of soft ferromagnetic signals. Magnetic research proves that the iron ring film has time reversal symmetry breaking.

[0048] SHG characterization The variable power SHG data were measured using the WITec 300R Raman measurement system, such as Fig.10 As shown. Under 1064 nm wavelength excitation, the film can emit a 532 nm frequency-overshoot peak, and although the power changes, the signal intensity increases significantly. By confirming that the net signal intensity is proportional to the square of the power, it can be confirmed that the signal is a SHG signal. Only non-centrosymmetric structures have SHG signals, which indicates that there is a breaking of spatial inversion symmetry in the ferroxene film.

[0049] In summary, the present invention provides an actinide iron ring body film and its preparation method and property research, and develops two reduction methods for uranyl cyclodextrin film for the first time: irradiation reduction and LED light reduction, which achieves efficient reduction and stable retention of uranyl. By measuring magnetism and SHG, it is proved that the crystal film has the characteristics of time reflection and space inversion symmetry breaking, and has the basic property requirements of the iron ring body, and is a potential iron ring body film material.

[0050] Finally, it should be noted that the purpose of publishing the embodiments is to help further understand the present invention. Those skilled in the art should understand that various substitutions and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the present invention should not be limited to the contents disclosed in the embodiments, and the scope of protection claimed by the present invention shall be subject to the scope defined in the claims.

Claims

1. An actinide iron ring thin film material, characterized in that: The invention relates to a crystalline film prepared by a spin coating method, wherein the chemical components thereof include cyclodextrin, actinyl ions and alkali metal ions, wherein the actinyl ions are selected from UO2 + , NpO2 2+ , NpO2 + ,PuO2 2+ , AmO2 2+ , CmO2 2+ One or more of; the alkali metal ion is selected from Li + , Na + , K + , Rb + , Cs + One or more of .

2. The actinide iron ring thin film material according to claim 1, characterized in that: The cyclodextrin is α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin or macrocyclodextrin.

3. The actinide iron ring thin film material according to claim 1, characterized in that: The actinide iron ring film material has strong iron ring order, and the order transition temperature is above room temperature.

4. The method for preparing the actinide iron ring thin film material according to any one of claims 1 to 3, characterized in that: First, a mother solution containing actinyl nitrate, cyclodextrin and alkali metal hydroxide is spin-coated on a substrate to prepare an actinyl cyclodextrin crystal film; then, the actinide cyclodextrin crystal film is treated by irradiation reduction or photoreduction, or no reduction is required to obtain an ferrocyclic film; wherein, for the uranyl cyclodextrin crystal film, hexavalent uranyl is reduced to pentavalent uranyl by irradiation or LED light to obtain an ferrocyclic film; and for other actinyl cyclodextrin crystal films, no reduction is required to obtain an ferrocyclic film, or actinyl ions are reduced by irradiation or LED light to obtain a stable ferrocyclic film.

5. The preparation method according to claim 4, characterized in that: The solvent of the mother solution is ultrapure water, wherein the molar ratio of actinyl nitrate: cyclodextrin: alkali metal hydroxide is in the range of 1:2:10 to 1:2:50, and the concentration of actinyl nitrate is 10-80 mM.

6. The preparation method according to claim 4, characterized in that: The substrate is a single crystal silicon wafer, quartz glass, sapphire or a metal substrate.

7. The preparation method according to claim 6, characterized in that: A single crystal silicon wafer is used as the spin coating substrate, and the silicon wafer is chemically cleaned with piranha solution before spin coating.

8. The preparation method according to claim 4, characterized in that: The spin coating speed is 1000-10000 rpm, the spin coating time is 0.5-10 min, and after spin coating, the coating is dried naturally or heated to dry at a temperature of less than 100°C.

9. The preparation method according to claim 4, characterized in that: The radiation reduction method uses γ-rays as the emission rays, the irradiation dose is 100 to 800 kGy, and the irradiation dose rate is 100 to 800 Gy / min; the photoreduction method uses white light LED as the light source, the light wavelength range is between 400 and 700 nm, the light source power is 10 to 100 mW, and the irradiation time is 1 to 100 h.

10. Use of the actinide iron ring thin film material according to any one of claims 1 to 3 in the preparation of electronic devices.

Citation Information

Patent Citations

  • Bismuth ferrite film doped with lanthanide metal atoms at A site and preparation method thereof

    CN115504684A

  • Atinide series soft iron hoop body material and preparation method thereof

    CN116836406A

  • Cold spray of brittle materials

    US20200157689A1